(untitled) (Economic and Political Thought, 2015)
The Transatlantic Trade and Investment Partnership is an undertaking that can completely change the contemporary structure of global trade relations. Due to the role and importance of the economic exchange between the parties to the future free trade agreement: the European Union and the United States, the rules of liberalisation negotiated by them can change the present, universal order within the WTO system. Having taken into consideration the increasing number of agreements that create new free trade areas, one can say that the thesis that, as a result of that phenomenon, there is an increasing fragmentation of global trade seems to be confirmed in practice. What the benefits are going to be will depend on the balance of trade changes and development. At the same time, what the costs are going to be for particular parties to the global economic exchange will mainly depend on their national economies’ ability to meet challenges adequately. It is well known that developed countries and their multinational companies cope with such conditions best. New rules of global economic exchange are created and the positive effects of these changes in that exchange concentrate in this area. Although there are attempts to make developing countries beneficiaries of the world trade liberalisation, e.g. the Bali Package within the WTO, the positive effect of these initiatives is more hypothetical than real for them.